The Thomas Mans, their Books, and Jesus College Librarianship. (17th March 2020) - Hanna, Ralph
Abstract: On 21 January 1684/5, Thomas Man, a thirty-year-old Fellow, made a substantial donation of manuscripts to Jesus College, Cambridge. These included a substantial number of books from medieval institutional collections, including at least thirty-one from Durham cathedral priory. The essay ascertains the extent of the donation, a discussion intertwined with that of librarianship at Jesus College. It also offers information about the collection activity of Man's father, also Thomas, who assembled the collection, and points to several Man books now preserved elsewhere.